On the removal of silver and antimony radionuclides from radioactive liquid waste by some classical means. (7th February 2008) - Jan, F.
After partial upgrading of a research reactor at the Pakistan Institute of Nuclear Science and Technology, Islamabad, some waste effluents having 110mAg and 124Sb with higher activity levels than the disposal limits piled up because the waste storage capacity was not yet enhanced. Experimental work was conducted to arrive at some optimum procedure for the treatment of the waste to ensure smooth reactor operation. Different classical reagents and methods, e.g., using tellurium as a carrier of silver; chemical reduction and isotopic exchange of silver; using ion exchange resins, charcoal and manganese dioxide as cation adsorber and filtration of radiocolloids of silver, were tested. These experiments yielded interesting results and a few of them offered very cost- and time-effective decontamination of the wastewater, which is usually difficult to achieve through chemical treatment processes. Some of these experiments are presented here.